The Effect Of Local Microorganisms From Coconut Husk On The Growth Of Oil Palm (Elaeis Guineensis Jacq.) In The Main Nursery - Wulan Kumala Sari; Risa Prima Yelli (Jurusan Budidaya Perkebunan, 2023)
One coconut produces an average of 0,4 kg of coconut husk that contain N, P, K, Ca, Mg, and Na elements. Liquid waste in the form of local microorganisms’ results coconut husk fermentation is residue from households or industries that potentially as liquid fertilizer. The objectives of this study were to determine the effect of local microorganisms from coconut husk on the growth of oil palm (Elaeis guineensis Jacq.) in the main nursery and to obtain the best dose of its local microorganisms. The research was carried out in the nursery of the Agricultural Technology Research Center located at Gunung Medan, Dharmasraya on May until August 2018. Experiments were arranged by Completely Randomized Design (CRD) with 6 treatments and 6 replications. Data obtained were analyzed of variance at 5% and further analyzed using Duncan’s New Multiple Range Test (DNMRT) for statistically significant results. The results showed that the application of several doses of liquid organic fertilizer (local microorganisms) from coconut husk fermentation gave an effect on the growth of oil palm in the main nursery especially on the variable of shoot dry weight, root dry weight and shoot root ratio, with the best dose of it was on 100 ml.